Strengthening Governance for Sustainability : The Role of ESG Committees in Enhancing Corporate Sustainability Performance in Indonesia - Meifaza Ainur Rosyidah; Sri Ningsih (Politeknik Ganesha Medan, 2025)
Purpose: This study examines the impact of Environmental, Social, and Governance (ESG) committees on corporate sustainability performance in Indonesia. It evaluates whether ESG committees enhance sustainability reporting and corporate transparency, particularly in industries with high environmental and social risks. Methodology/approach: Using an Ordinary Least Squares (OLS) regression with a cluster approach, this study analyzes 907 non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. Robustness tests such as Coarsened Exact Matching (CEM) and fixed-effects regression ensure result reliability. Findings: The findings reveal a significant positive relationship between ESG committees and corporate sustainability performance. Firms with ESG committees display higher ESG disclosure scores, especially in environmental and social aspects. This effect is more evident in high-risk industries and during crises like the COVID-19 pandemic. Practical implications: This study highlights the need for regulatory frameworks that encourage ESG committees to enhance corporate accountability and sustainability. It provides insights for policymakers, investors, and executives on improving sustainability governance. Originality/value: This research contributes to ESG governance literature with empirical evidence from an emerging market. It incorporates industry-specific and crisis-period analyses, offering a deeper understanding of ESG committee effectiveness.